Serious limitations of the current strategy to control Soil-Transmitted Helminths and added value of Ivermectin/Albendazole mass administration: A population-based observational study in Cameroon. - Linda Djune-Yemeli; Hugues C Nana-Djeunga; Cédric G Lenou-Nanga; Cyrille Donfo-Azafack; André Domche; Floribert Fossuo-Thotchum; Yannick Niamsi-Emalio; Francine Ntoumi; Joseph Kamgno (Public Library of Science (PLoS), 2020)
Background Soil-transmitted helminth (STH) infections remain a public health concern in sub-Saharan Africa. School-based mass drug administration (MDA) using the anthelminthic drug Mebendazole/Albendazole have succeeded in controlling morbidity associated to these diseases but failed to interrupt their transmission. In areas were filarial diseases are co-endemic, another anthelminthic drug (Ivermectin) is distributed to almost the entire population, following the community-directed treatment with ivermectin (CDTI) strategy. Since Ivermectin is a broad spectrum anthelmintic known to be effective against STH, we conducted cross-sectional surveys in two health districts with very contrasting histories of Ivermectin/Albendazole-based PC in order to investigate whether CDTI might have contributed in STH transmission interruption. Methodology Cross-sectional surveys were conducted in two health districts with similar socio-environmental patterns but with very contrasting CDTI histories (Akonolinga health district where CDTI was yet to be implemented vs. Yabassi health district where CDTI has been ongoing for two decades). Stool samples were collected from all volunteers aged >2 years old and analyzed using the Kato-Katz technique. Infections by different STH species were compared between Akonolinga and Yabassi health districts to decipher the impact of Ivermectin/Albendazole-based MDA on STH transmission. Principal findings A total of 610 and 584 participants aged 2-90 years old were enrolled in Akonolinga and Yabassi health districts, respectively. Two STH species (Ascaris lumbricoides and Trichuris trichiura) were found, with prevalence significantly higher in Akonolinga health district (43.3%; 95% CI: 38.1-46.6) compared to Yabassi health district (2.5%; 95% CI: 1.1-5.1) (chi-square: 90.8; df: 1; p < 0.001). Conclusion/significance These findings (i) suggest that Mebendazole- or Albendazole-based MDA alone distributed only to at-risk populations might not be enough to eliminate STH, (ii) support the collateral impact of Ivermectin/Albendazole MDA on A. lumbricoides and T. trichiura infections, and (iii) suggest that Ivermectin/Albendazole-based PC could accelerate STH transmission interruption.